2022
DOI: 10.1038/s41598-021-04128-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of controlling nutritional status score (CONUT) in evaluating outcome of postoperative patients with gastric cancer

Abstract: The stomach is the main digestive organ in humans. Patients with gastric cancer often develop digestive problems, which result in poor nutrition. Nutritional status is closely related to postoperative complications and quality of life (QoL) in patients with gastric cancer. The controlling nutritional status (CONUT) score is a novel tool to evaluate the nutritional status of patients. However, the relationship of the CONUT score with postoperative complications, QoL, and psychological status in patients with ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…Clinical data, including demographic information, medical history, laboratory tests, postoperative complications, lengths of hospital stay (LOS), and cost were collected and analyzed. Postoperative complications (PPC) were graded according to the Clavien-Dindo (CD) classification [15], and grade II or higher were regarded as complications [16].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical data, including demographic information, medical history, laboratory tests, postoperative complications, lengths of hospital stay (LOS), and cost were collected and analyzed. Postoperative complications (PPC) were graded according to the Clavien-Dindo (CD) classification [15], and grade II or higher were regarded as complications [16].…”
Section: Introductionmentioning
confidence: 99%
“…All the above issues tend to aggravate the malnutrition state of the patient, forming a vicious circle. Xiao et al reported that nutritional deficiencies following gastric cancer surgery directly impact the treatment effect of patients and can easily lead to adverse clinical outcomes (22). In this study, the timepoint of three months after surgery was selected as the period for assessment of malnutrition and as the basis for grouping.…”
Section: Discussionmentioning
confidence: 99%
“…Although malnutrition has been investigated with increasing interest in recent years, it is one of the hallmarks of frailty 6,8,9,13,14 . Initially, several scores were developed related to malnutrition, which was associated with poor clinical outcomes in cancer patients 8,15,16 . Additionally, malnutrition has also been associated with mortality, morbidity, and disease severity in cardiovascular disease 6,10,13,14,17–21 .…”
Section: Discussionmentioning
confidence: 99%